The Relationships Between Plasma Adrenomedullin and Endothelin-1 Concentrations and Doppler Echocardiographic Indices of Left Ventricular Function During Static Exercise in Healthy Men - Krzemiński, Krzysztof (Akademia Wychowania Fizycznego w Katowicach, 2012)
Our previous study showed a significant relationships between static exercise-induced changes in plasma adrenomedullin (ADM) and those in endothelin-1 (ET-1), noradrenaline (NA) and pre-ejection period/left ventricular ejection time ratio (PEP/LVET) in older healthy men. It is hypothesized that ADM, ET-1, NA and adrenaline (A) may function as endogenous regulators of cardiac function by modulating myocardial contractility during static exercise. The present study was undertaken to assess the relationships between exercise-induced changes in plasma ADM, ET-1, NA, A concentrations and those in ascending aortic blood flow peak velocity (PV) and mean acceleration (MA) measured by Doppler echocardiography in 24 healthy older men during two 3-min bouts of handgrip at 30% of maximal voluntary contraction, performed alternately with each hand without any break between the bouts. Plasma ADM, ET-1, NA and A as well as heart rate (HR), blood pressure (BP), PV and MA were determined. During handgrip, plasma ADM, ET-1, NA and A as well as HR, BP increased, whereas PV and MA decreased. The increases in plasma ADM correlated positively with those in ET-1, NA and diastolic BP, and correlated negatively with changes in PV (r= −0.68) and MA (r= −0.62). The increases in plasma ET-1 correlated positively with those in NA and BPs and correlated negatively with changes in PV (r= −0.67) and MA (r= −0.60). The results of this study suggest that in healthy older men the exercise-induced changes in plasma ADM, ET 1 and catecholamines are related to alterations in left ventricular contractile state and may co-operatively counteract age-related deterioration of cardiac performance in men.